THE IMPORTANCE OF ETHICS IN PEDIATRICS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the doctor's vigilance towards the patient, the medical worker's treatment of the patient, being humble. The competence of the doctor in communicating with loved ones of the patient and explaining to them the condition of the patient. It has always been said that medical personnel improve their skills.